EFFECTIVENESS OF SIMANTRI APPLICATION AND ITS ENFLUENCE ON THE IMPROVEMENT OF FARMER’S INCOME IN BALI - Maha Putra Sanjaya, Agus; Suparta, I Nyoman; Lanang Oka, I. Gst.; Gaga Partama, I.B. (E-Journal Of Animal Science Udayana University; Vol 3, No 1, Tahun 2014, 2014)
A survey was carried out to analyze  the effectiveness level of Simantri application and the effectiveness of Simantri application on increasing farmer’s income. Structured questionaires were used to obtain information from 138 respondents consisting of chairmans, secretaries, and treasurers of forty-six groups of Simantri from 2009-2010. The groups of Simantri selected by purposive sampling method. Data obtained were analyzed by descriptive method and statistic analysis. Results indicated that : less than a quarter of respondents (23.92%) effective in Simantri application, while 105 respondents (76.08%) was less effective. Effectiveness of Simantri application improved farmer’s income in Bali.